Peranan Lagu Anak-Anak Sebagai Media Persuasif Untuk Mempengaruhi Perilaku Positif Anak Usia Dini Di Kota Surakarta - Dewi Agustini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Children's songs are usually cheerful and reflect noble ethics, poetry contains things that are usually done by children. Singing a child's song is a way that can be used as a medium for delivering messages or character education in the daily lives of young children (1-6 years). His intelligence is developing rapidly, which is usually called the